Skating technique detection in cross-country skiing using a kinematic global navigation satellite system. The difference between fast and slow gliding skies - Masaki, T.; Naoto, M.; Shunya, U.; Linnamo, V.; Lindinger, S.; Stöggl, T. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Technique detection in both classical and skating in cross-country skiing is an essential issue in improving competitive performance (Takeda et al., 2019). In this study, we tried to detect skating sub-techniques, V1, V2, V2a, and others (turning or gliding) using a kinematic global navigation satellite system (GNSS).